Coping Strategies in Managing Multiple Roles for Sandwich Generation Nurses: A Phenomenological Study - Utari Wardhani; Galuh Eka Safitri; Umi Eliawati (Talenta Publisher, 2026)
Sandwich generation nurses are known to experience considerable psychological pressure due to the dual responsibilities at home, alongside economic demands and heavy professional workloads. These overlapping roles often create time constraints and increased stress, underscoring the importance of effective coping strategies to maintain mental well-being. Therefore, the present study aimed to explore the coping strategies used by sandwich generation nurses to manage multiple roles. A qualitative phenomenological method was adopted, involving 10 sandwich generation nurses working at a Private Hospital in Batam. The participants were selected using the snowball sampling technique. Data were collected through in-depth interviews and reviewed using thematic content analysis. The entire analysis process identified four main themes. This included (1) managing competing professional and family responsibilities, (2) searching for interpersonal and institutional support, (3) engaging in restorative self-care activities, alongside (4) cultivating meaning and positive reframing. Occupational and emotional challenges were addressed through adaptive coping strategies that promoted emotional regulation, resilience, and psychological stability. Additionally, the results showed that effective coping strategies played a crucial role in maintaining nurses' mental well-being. The cultivation of gratitude and the maintenance of a positive mindset have evolved as significant strategies for helping sandwich generation nurses adapt to the pressures of multiple role demands. Future studies are recommended to inform the development of targeted policies and interventions to enhance the well-being of sandwich generation nurses. Keyword: Coping skills, Role conflict, Resilience, Self-care, Hospitals